Romanticism and the Anglo-Hispanic imaginary - Almeida, Joselyn M. (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2010)
" ... the authors assess British Romanticism's creative and polemical engagements with the Peninsular War, the bid of Spanish American colonies to establish independence with British support, and the impact of travel narratives about Spain and the Americas."--Page 4 of cover.